Enhancing positive perceptions of aging by savoring life lessons. (3rd June 2019) - Smith, Jennifer L.; Bryant, Fred B.
ABSTRACT: Objectives: This study examined the effects of savoring valuable life lessons on perceptions of aging and on well-being among older adults. Method: A total of 303 adults (mean age = 68.12 years) were randomly assigned to one of three experimental conditions: savoring life lessons ( n = 95), reflecting on negative aspects of aging ( n = 129), or untreated-control condition ( n = 79). Participants in the savoring condition wrote about a valuable lesson they had learned in growing older, whereas participants in the negative-aging condition wrote about physical losses they had experienced in aging. Results: After controlling for baseline happiness, health, gender, and age, participants who savored valuable life lessons reported greater positive perceptions of aging and life satisfaction, compared to participants in the negative-aging and untreated-control conditions. There were no differences across conditions in negative perceptions of aging or in anxiety. Conclusion: These findings suggest that savoring valuable life lessons could be an effective addition to psychoeducational programs designed to improve perceptions of aging.